2017
DOI: 10.5455/jbh.20170705063150
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation of outpatient healthcare services among elderly people with Hypertension in Ghana

Abstract: Background: Aging population has become one of the most pressing demographic phenomena in the world. The situation presents challenges to the health sector due to the higher number of chronic diseases (e.g., hypertension) that the situation presents. One of the major risk factors for cardiovascular diseases is hypertension, and its management may reduce such risk. Therefore, this study examines the factors affecting outpatient healthcare utilization among the elderly for the management of hypertension. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
1
0
1
1
Order By: Relevance
“…Young people with disabilities who had subscribed to health insurance recorded a higher probability of SRHS utilisation compared with those who had not subscribed. This finding confirms those of other previous studies, which revealed that ownership of health insurance affects utilisation of healthcare services (Boachie 2017 ; Kyilleh et al 2018 ; Van der Wielen, Channon & Falkingham 2018 ). One of the key barriers to non-utilisation of healthcare services is the direct financial cost of healthcare (Dhillon et al 2012 ).…”
Section: Discussionsupporting
confidence: 92%
“…Young people with disabilities who had subscribed to health insurance recorded a higher probability of SRHS utilisation compared with those who had not subscribed. This finding confirms those of other previous studies, which revealed that ownership of health insurance affects utilisation of healthcare services (Boachie 2017 ; Kyilleh et al 2018 ; Van der Wielen, Channon & Falkingham 2018 ). One of the key barriers to non-utilisation of healthcare services is the direct financial cost of healthcare (Dhillon et al 2012 ).…”
Section: Discussionsupporting
confidence: 92%
“…Based on this research, 24.1% of the elderly with hypertension used outpatient services. Our finding was lower than that found in China (54.9%) (21) and Ghana (78.61%) (22). The statistical examination shows that gender, insurance status, perception of health status, economic status, number of chronic diseases, marital status, limit in physical activity, and region significantly contribute to the utilization of outpatient services.…”
Section: Discussioncontrasting
confidence: 79%
“…Penelitian lain dilakukan Boachie (2017) Selain faktor individual, Andersen (2008) menyatakan bahwa faktor kontekstual juga menjadi faktor yang dapat memengaruhi perilaku pemanfaatan pelayanan kesehatan yang dilakukan. Umur merupakan salah satu komponen predisposisi yang dapat memengaruhi perilaku pemanfaatan pelayanan kesehatan (Andersen & Newman, 2005).…”
Section: Chukwudiunclassified